Pyrolysis Temperature Effect on Volume and Chemical Composition of Liquid Volatile Matter of Durian Shell - Waode O.S. Ilmawati; M. Jahiding; Waode O.S. Musnina (UPT Penerbitan Universitas Jember, 2016)
Durian shell is one of the organic waste that has not been used widely. Durian shell contains cellulose, hemicellulose and lignin thus potentially processed as liquid volatile matter (LVM). The purpose of this study are determine the effect of temperature on volume and compound of LVM durian shell. Durian shell stored from a region producer durian then dried. Farther dry durian shell heated in a pyrolysis reactor on a temperature varied at 400○C, 500○C, 600○C and 700○ C. Smoke from reactor pyrolysis condensed produce a certain volume of LVM. LVM volume durian shell was measured using a measuring cup and content of LVM has been characterized using gas chromatography (GC). Product of LVM durian shell at each temperature pyrolysis yielding different volume although the difference was not significant, respectively 52 ml, 55 ml, 57 ml and 58 ml. Type of compound and the percentage area of durian shell LVM is different at each temperature pyrolysis. LVM durian shell containing ammonia, hexane, acetic acid, propanone, cyclomethanodion, methanol and phenol.